Plant-environment interactions: from sensory plant biology to active plant behavior - Baluška, F. (Springer, 2017)
Mechanical integration of plant cells / Anna Kasprowicz ... [et al.] -- Root behavior in response to aluminum toxicity / Charlotte Poschenrieder ... [et al.] -- Communication and signaling in the plant-fungus symbiosis: the mycorrhiza / Pascale Seddas ... [et al.] -- Role of y-Aminobutyrate and y-Hydroxybutyrate in plant communication / Barry J. Shelp, Wendy L. Allan, and Denis Faure -- Hemiparasitic plants: exploiting their host's inherent nature to talk / John I. Yoder, Pradeepa C. Gunathilake, and Denneal Jamison-McClung -- Host location and selection by holoparasitic plants / Mark C. Mescher, Jordan Smith, and Consuelo M. DeMoraes -- Plant innate Immunity / Jacqueline Monaghan, Tabea Weihmann, and Xin Li -- Airborne induction and priming of defenses / Martin Heil -- Chemical signaling during induced leaf movements / Minoru Ueda and Yoko Nakamura -- Aposematic (warning) coloration in plants / Simcha Lev-Yadun -- Deceptive behavior in plants. I. Pollination by sexual deception in Orchids: a host-parasite perspective / Nicolas J. Vereecken -- Deceptive behavior in plants. II. Food deception by plants: from generalized systems to specialized floral mimicry / Jana Jersáková, Steven D. Johnson, and Andreas Jürgens -- Cognition in plants / Paco Calvo and Fred Keijzer -- Memorization of abiotic stimuli in plants: a complex role for calcium / Camile Ripol ... [et al.] -- Plants and animals: convergent evolution in action? / František Baluška and Stefano Mancuso.